Tritordeum, barley landraces and ear photosynthesis are key players in cereal resilience under future extreme drought conditions - Ander Yoldi-Achalandabaso; Aitor Agirresarobe; Artūrs Katamadze; Giulia Burini; Omar Vergara-Díaz; Mariana Mota; Cristina Oliveira; Usue Pérez-López; Rubén Vicente (Plant Stress, 2025)
Drought is the main factor limiting cereal production in the Mediterranean basin and Climate Change will exacerbate its effects. Among the strategies to mitigate Climate Change impact on cereal production, we highlight the development of drought-resilient crops better adapted to future extreme conditions, either by i) using heritage germplasm (e.g., landraces) or ii) developing novel species (e.g., crop hybrids). Our study aimed to identify key functional traits and stress-tolerant germplasm to contribute to designing drought-resilient crops under future Mediterranean climatic conditions. For that, we conducted an innovative approach combining a late-sowing field trial with two contrasting water regimes to simulate future extreme drought conditions, the use of high-throughput phenotyping devices and an infrared gas analyser to characterise leaf and ear photosynthesis, biochemistry, growth, and stress responses during the reproductive stage, and a novel linear mixed-effects model to integrate these results with final agronomical data. Modern durum wheat and barley, barley landraces and tritordeum varieties were grown and evaluated as individual plants. Our results identified barley landrace SBCC010 and tritordeum Coique as promising resilient germplasm. These genotypes showed a grain set maintenance and a higher allocation of resources to the ears compared to modern varieties, higher leaf and ear greenness, and ear photosynthesis and thermostability during the reproductive stage, particularly under stress conditions. We conclude the necessity of including ear photosynthesis in the breeding programs relying on adaptive germplasm as barley landraces and novel cereal hybrids as tritordeum to design drought-resilient cereals for future extreme Mediterranean environments.